Flow Cytometric Measurement of Efflux in Candida Species. Issue 1 (13th October 2020) - Iyer, Kali R.; Robbins, Nicole; Cowen, Leah E.
Abstract: A technique to assess the ability of distinct Candida strains to efflux substrates, as well as to compare the effectiveness of efflux inhibitors, is important for analysis of antifungal drug resistance mechanisms and the mode of action of antifungals. We describe a method that measures the ability of Candida species to extrude the fluorescent dye Nile red as an output for efflux activity. This involves exposing cells to Nile red and using flow cytometry to quantify cellular fluorescence, enabling numerous samples to be processed in a limited time frame. This protocol provides a simple, yet effective method for quantifying efflux in drug‐resistant Candida species. © 2020 Wiley Periodicals LLC Basic Protocol 1 : Growth and sample preparation of stained Candida Basic Protocol 2 : Quantitative measurement of fluorescence by flow cytometry Alternate Protocol : Qualitative determination of fluorescence using microscopy